Cryptochromes Mediate Intrinsic Photomechanical Transduction in Avian Iris and Somatic Striated Muscle - Margiotta, Joseph F.; Howard, Marthe J. (Frontiers in Physiology, 2020)
Irises isolated from the eyes of diverse species constrict when exposed to light. Depending on species this intrinsic photomechanical transduction response (PMTR) requires either melanopsin or cryptochrome (CRY) photopigment proteins, generated by their respective association with retinoid or flavin adenine dinucleotide (FAD) chromophores. Although developmentally relevant circadian rhythms are also synchronized and reset by these same proteins, the cell type, mechanism, and specificity of photomechanical transduction (PMT) and its relationship to circadian processes remain poorly understood. Here we show that PMTRs consistent with CRY activation by 430 nm blue light occur in developing chicken iris striated muscle, identify relevant mechanisms, and demonstrate that similar PMTRs occur in striated iris and pectoral muscle fibers, prevented in both cases by knocking down CRY gene transcript levels. Supporting CRY activation, iris PMTRs were reduced by inhibiting flavin reductase, but unaffected by melanopsin antagonism. The largest PMTRs paralleled the developmental predominance of striated over smooth muscle fibers, and shared their requirement for extracellular Ca2+ influx and release of intracellular Ca2+. Photo-stimulation of identified striated myotubes maintained in dissociated culture revealed the cellular and molecular bases of PMT. Myotubes in iris cell cultures responded to 435 nm light with increased intracellular Ca2+ and contractions, mimicking iris PMTRs and their spectral sensitivity. Interestingly PMTRs featuring contractions and requiring extracellular Ca2+ influx and release of intracellular Ca2+ were also displayed by striated myotubes derived from pectoral muscle. Consistent with these findings, cytosolic CRY1 and CRY2 proteins were detected in both iris and pectoral myotubes, and knocking down myotube CRY1/CRY2 gene transcript levels specifically blocked PMTRs in both cases. Thus CRY-mediated PMT is not unique to iris, but instead reflects a more general feature of developing striated muscle fibers. Because CRYs are core timing components of circadian clocks and CRY2 is critical for circadian regulation of myogenic differentiation CRY-mediated PMT may interact with cell autonomous clocks to influence the progression of striated muscle development.